The Joint Arctic Weather Stations Science and Sovereignty in the High Arctic, 1946-1972 - Heidt, Daniel (Northern Lights, 2022)
This is the first systematic account of the Joint Arctic Weather Stations (JAWS), a collaborative science program between Canada and the United States that created a distinctive state presence in the Canadian Arctic Archipelago from 1946-1972. These five meteorological stations, constructed at Eureka, Resolute, Isachsen, Mould Bay, and Alert, became remote hubs for science and sovereignty, revealing the possibilities and limits of modernity in the High Arctic. Drawing on extensive archival evidence, unpublished personal memoirs, and interviews with former JAWS personnel, this book systematically analyzes the diplomatic, scientific, social, environmental, and civil-military dimensions of this binational program. From the corridors of power in Washington and Ottawa to everyday life at the small outposts, The Joint Arctic Weather Stations explores delicate statecraft, changing scientific practices, as well as the distinctive station cultures that emerged as humans coped with isolation in polar environments.